2018
DOI: 10.1002/pros.23504
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an IL‐1‐induced gene expression pattern in AR+ PCa cells that mimics the molecular phenotype of AR PCa cells

Abstract: Our data supports that IL-1 reprograms AR PCa cells to mimic AR PCa gene expression patterns that favor AR-targeted treatment resistance and cell survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 50 publications
3
60
0
Order By: Relevance
“…We found that IL‐1 alone or in the HS‐5 CM milieu is sufficient to repress AR and induce p62 mRNA and protein accumulation in PCa cell lines. To determine if IL‐1 signaling is sufficient to mediate HS‐5 BMSC paracrine modulation of ERα, PR, p62, and/or autophagy in ERα + /PR + BCa cell lines, we blocked IL‐1 signaling in MCF7 and T47D cells with the IL‐1Ra.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…We found that IL‐1 alone or in the HS‐5 CM milieu is sufficient to repress AR and induce p62 mRNA and protein accumulation in PCa cell lines. To determine if IL‐1 signaling is sufficient to mediate HS‐5 BMSC paracrine modulation of ERα, PR, p62, and/or autophagy in ERα + /PR + BCa cell lines, we blocked IL‐1 signaling in MCF7 and T47D cells with the IL‐1Ra.…”
Section: Resultsmentioning
confidence: 78%
“…We found that IL‐1 signaling downregulates AR in PCa cell lines concomitant with the induction of several prosurvival, progrowth pathways that may contribute to treatment resistance, such as p62 signaling . p62 is a multidomain scaffold protein that has been shown to be cytoprotective for multiple different cancer types and p62 mediates various prosurvival signaling cascades, including autophagy .…”
Section: Introductionmentioning
confidence: 95%
“…IL-1 conferred 350-gene signature is enriched in genes and pathways that promote BCa and PCa survival and progression. We have previously shown that HR low/-BCa 19 and PCa 18,42 cells are enriched when HR + cells are exposed to IL-1. Here, we sought to compare the gene expression pattern overlap between cells that lose hormone receptors in response to IL-1 to cells that are intrinsically HR -.…”
Section: Discussionmentioning
confidence: 95%
“…IL-1 is elevated in BCa and PCa tumors [8][9][10][11][12][13] and correlates with low or lost ERα or AR accumulation 10,[14][15][16][17] . We discovered that IL-1 downregulates ERα and AR levels in HR + BCa and PCa cell lines concomitant with the upregulation of pro-survival proteins that are basally high in HRcell lines 18,19 . Thus, IL-1 may select for and promote the evolution of treatment resistant cells, and our findings provide an opportunity to discover novel therapeutic targets for HR-independent BCa and PCa.…”
mentioning
confidence: 99%
See 1 more Smart Citation